Strategi Pemberdayaan Masyarakat Oleh Badan Wakaf Uang Muhammadiyah (BWUM) Sumatera Barat - Thaheransyah Thaheransyah (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
This study aims to reveal how the strategy of the West Sumatra Muhammadiyah Money Waqf Board in community empowerment. This type of research is field research, using qualitative methods through a descriptive approach. The data sources used are primary data and secondary data from BWUM West Sumatra. The results of this study indicate that the community empowerment strategy is carried out by developing cash waqf assets, including; (1) Investing in waqf funds in syari'ah financial institutions, (2) cultivating organic catfish, (3) managing sugar cane fields, and (4) establishing a blessing trading business. Supporting factors Community Empowerment include; There is support and trust from the community for Muhammadiyah to manage waqf for more than 1 century, qualified human resources (HR) and support for the management of waqf development, cash waqf is more productive so that it can contribute and real solutions to the problems and crises that are being faced by people and nation today. The inhibiting factor Community Empowerment is that there are still many people who do not know cash waqf so that socialization is still needed, the role of the leadership in managing BWUM has not been maximized due to time constraints and work in other places, the limited amount of waqf funds available due to the lack of awareness of the community to donate money, Some of the administrators live outside the city.